2021
DOI: 10.2514/1.j059335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Roughness Geometry on Boundary-Layer Transition and Far-Field Noise

Abstract: to initiate your request. See also AIAA Rights and Permissions www.aiaa.org/ randp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Wind-turbine and gas-turbine blades erode due to particle impact, resulting in the formation of surface roughness close to the leading edge [11,12]. Previous research has shown that the type of surface roughness and its height have a direct influence on the transition onset and the turbulent boundary layer development [10,[13][14][15][16][17], consequently also affecting the trailing edge noise. Braslow [17] stated that for two-dimensional surface roughness, e.g., zigzag strips, spots of turbulence begin to move forward of the natural position of transition when a critical value of Reynolds number based on the trip height is reached.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wind-turbine and gas-turbine blades erode due to particle impact, resulting in the formation of surface roughness close to the leading edge [11,12]. Previous research has shown that the type of surface roughness and its height have a direct influence on the transition onset and the turbulent boundary layer development [10,[13][14][15][16][17], consequently also affecting the trailing edge noise. Braslow [17] stated that for two-dimensional surface roughness, e.g., zigzag strips, spots of turbulence begin to move forward of the natural position of transition when a critical value of Reynolds number based on the trip height is reached.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was also a large spanwise coherence in the flow, which they attributed to the surface roughness elements. Ye [15] measured the transition point of the boundary layer by means of infrared thermography, observing that the transition location for a zigzag strip of 0.3 mm high moves closer to the strip as the free-stream velocity increases. This occurs because for higher velocities, the boundary layer becomes thinner, making the roughness height more comparable with the boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations